Contributions of perioperative nursing to patient safety in the operating room: an integrative review - Santos, Wanderson Paiva dos (2023)
The objective was to identify the contributions of perioperative nursing to patient safety in the operating room. Methods: This is an integrative literature review, using the PICO strategy to search for articles. Results: Most studies pointed out the implementation of the safe surgery checklist as the main contribution of perioperative nursing. Other authors point out nursing contributions in partnership with other members of the health team. The contributions are related to the patient's emotional preparation during the surgery; perioperative pause to improve handoff and; nursing interventions in the operating room to reduce infection rates. Conclusion: This study showed that perioperative nursing directly contributes to anesthetic-surgical patient safety through management and care interventions and also through effective communication with the multidisciplinary team. It is important to carry out empirical studies that demonstrate the contributions of perioperative nursing to patient safety in the surgical environment.